(3JMUjd GdeQGe ef JGQjN GdHdO GdMQGes - (3Jbj GdOjf eMeO Hf CMeO Hf Ydj GdMSjfj GdaGSj,J (B832 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi haQ decI GdeMQeI CeG HYO aEfi CdbjJ JGQjNkG decI GdeTQaI Ydi feW JGQjNgG GdPi CdaI GdEeGe CHh GdhdjO eMeO Hf YHO Gddg Hf CMeO Hf eMeO GdCQRbi s
(3BNQgG (B:s
(3hcGf JCdjai ddKdGKI GdCHhGH GdCNjQg efg hgj GdehLhOI aj gPG GdJCdja s
(3GfJgi GdeUfa ef JCdja SfI (B819 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331s
Keywords: (3eJaQbGJs